2020
DOI: 10.1159/000509774
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Symptoms and Outcomes in Hospitalized Coronavirus Disease 2019 Patients

Abstract: Introduction: Gastrointestinal (GI) symptoms are increasingly being recognized in coronavirus disease 2019 (COVID-19). It is unclear if the presence of GI symptoms is associated with poor outcomes in COVID-19. We aim to assess if GI symptoms could be used for prognostication in hospitalized patients with COVID-19. Methods: We retrospectively analyzed patients admitted to a tertiary medical center in Brooklyn,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
87
4
9

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(105 citation statements)
references
References 23 publications
(41 reference statements)
5
87
4
9
Order By: Relevance
“…Patients infected with SARS-CoV-2 have an incubation period of 3-14 days with a mean period of 5 days (1,5,6). The most common symptoms of COVID-19 include fever, cough, fatigue, and bleeding (2,4,5,(7)(8)(9)(10)(11). Other symptoms include taste changes, headache, abdominal pain, diarrhea, and gastrointestinal bleeding (2,4,5,(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients infected with SARS-CoV-2 have an incubation period of 3-14 days with a mean period of 5 days (1,5,6). The most common symptoms of COVID-19 include fever, cough, fatigue, and bleeding (2,4,5,(7)(8)(9)(10)(11). Other symptoms include taste changes, headache, abdominal pain, diarrhea, and gastrointestinal bleeding (2,4,5,(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…The most common symptoms of COVID-19 include fever, cough, fatigue, and bleeding (2,4,5,(7)(8)(9)(10)(11). Other symptoms include taste changes, headache, abdominal pain, diarrhea, and gastrointestinal bleeding (2,4,5,(7)(8)(9)(10)(11). If left untreated, COVID-19 can lead to pneumonia, acute respiratory distress syndrome (ARDS), and acute respiratory failure resulting in death (1,5,6).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, among non-IBD patients, studies have reported diarrhea in 2-10%, nausea or vomiting in 1-10% and abdominal pain in 2.2-5.8% [ 60 - 62 ]. The diagnosis of IBD flare-up is challenging in the context of COVID-19, as the typical presenting features of IBD, such as diarrhea, abdominal pain and fever, along with elevated inflammatory markers, may also be secondary to COVID-19 [ 63 , 64 ]. However, rectal bleeding is not common in COVID-19 [ 63 ].…”
Section: Gi Manifestations Of Covid-19mentioning
confidence: 99%
“…[2][3][4][5] Beyond impacting neurological functions, SARS-CoV-2 infections have also been reported to affect the cardiovascular and gastrointestinal systems. [6][7][8][9] An especially troubling issue is that some symptoms can last for months beyond the primary infection, even in the absence of detectable virus. [10][11][12] It is unclear why some patients, often referred to as "long haulers," have prolonged effects.…”
Section: Introductionmentioning
confidence: 99%